Support plate structure, folding screen and preparation method of ultra-thin flexible glass layer
Patent Information
- Application Number
- CN202610882251.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-18
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2046-06-18
AI Technical Summary
[0003]然而,随着折叠屏向更小弯折半径、更高弯折寿命方向发展,PI层的固有缺陷逐渐凸显:PI材料在长期高频弯折后易产生不可逆的塑性形变和表面皱纹,这些形变无法弹性恢复,直接导致屏幕折痕不断加深,严重影响视觉体验
一、折痕表现显著改善,本申请采用化学强化处理的超薄柔性玻璃层替代传统的PI层,利用UTG材料高弹性模量和优异尺寸稳定性的固有特性,在弯折后能够迅速弹性恢复,不易产生不可逆的塑性形变。同时,UTG层的弯折区设置为连续弧形减薄结构,使弯折区中心线处厚度小于边缘厚度,避免了厚度突变导致的应力集中,进一步分散弯折应力。上述材料与结构的协同作用,使得折叠屏在反复弯折后折痕深度大幅降低,屏幕视觉平整度显著提升。
Smart Images

Figure CN122421636B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of flexible display technology, specifically relating to a support plate structure, a foldable screen, and a method for preparing an ultra-thin flexible glass layer. Background Technology
[0002] In the support plate structure of flexible OLED foldable screens, traditional solutions generally adopt a stacked design of "foldable adhesive / PI (polyimide) / foldable adhesive / metal support plate / Mylar hole-masking tape". Among them, the PI layer, as the core flexible buffer layer, is responsible for dispersing bending stress and adapting to the flexible deformation of the screen.
[0003] However, as foldable screens develop towards smaller bending radii and longer bending lifespans, the inherent defects of the PI layer are becoming increasingly apparent: PI materials are prone to irreversible plastic deformation and surface wrinkles after long-term high-frequency bending. These deformations cannot elastically recover, directly causing the screen creases to deepen continuously, severely impacting the visual experience. Therefore, how to fundamentally suppress the generation and accumulation of creases in the foldable screen support plate after repeated bending is a technical problem that urgently needs to be solved in this field. Summary of the Invention
[0004] In view of the above-mentioned defects or deficiencies in the prior art, a method for preparing a support plate structure, a folding screen and an ultra-thin flexible glass layer is provided.
[0005] In a first aspect, this application proposes a support plate structure, comprising: A multi-layer composite support plate is disposed on the back side of the OLED screen of the foldable screen; it includes, in sequence from the side closest to the OLED screen to the side furthest from the OLED screen: A first foldable adhesive layer, one side of which is bonded to the OLED screen body; An ultra-thin flexible glass layer, one side of which is bonded to the other side of the first foldable adhesive layer; A second foldable adhesive layer, one side of which is bonded to the other side of the ultrathin flexible glass layer; A metal support plate layer, one side of which is bonded to the other side of the second foldable adhesive layer; A hole-masking tape layer, one side of which is bonded to the other side of the metal support plate layer; The ultra-thin flexible glass layer is chemically strengthened, and the bending area of the ultra-thin flexible glass layer is set as a continuous arc-shaped thinning structure extending along the bending direction. The thickness of the arc-shaped thinning structure at the center line of the bending area is less than its thickness at the edge. The folded area of the metal support plate layer has multiple elongated through holes arranged at intervals along the bending direction; Both the first foldable adhesive layer and the second foldable adhesive layer are acrylic flexible adhesives.
[0006] According to the technical solution provided in this application, the thickness of the ultrathin flexible glass layer is 20μm to 40μm, and the surface compressive stress of the ultrathin flexible glass layer after chemical strengthening treatment is ≥600MPa and the Vickers hardness is ≥500HV.
[0007] According to the technical solution provided in this application, the width of the bending area of the arc-shaped thinning structure is 5mm to 40mm, the minimum thickness of the arc-shaped thinning structure at the center line of the bending area is 20μm to 30μm, and the edge thickness of the arc-shaped thinning structure is 40μm.
[0008] According to the technical solution provided in this application, the metal support plate layer is a foldable SUS 316L stainless steel or TA4 titanium alloy. The SUS 316L stainless steel has a molybdenum content of 2% to 3%, and the TA4 titanium alloy has a density of ≤4.5g / cm³ and a tensile strength of ≥860MPa. The width of the elongated through hole is 50μm to 150μm, and the length is 4mm to 12mm.
[0009] According to the technical solution provided in this application, the thickness of the first foldable adhesive layer and the second foldable adhesive layer are both 5μm to 15μm, and their glass transition temperature is ≤-20℃ and their elongation at break is ≥300%.
[0010] Secondly, this application proposes a foldable screen, including an OLED screen body and a support plate structure as described above disposed on the back side of the OLED screen body.
[0011] Thirdly, this application proposes a method for preparing an ultrathin flexible glass layer in the support plate structure as described above, comprising the following steps: Substrate pretreatment: Select raw glass substrates with a thickness of 50μm to 160μm and perform ultrasonic cleaning; Selective thinning: A mask is attached to the surface of the substrate, and fluoride coatings of different thicknesses are formed in the bending area through laser drilling and coating treatment. Then, hydrochloric acid mist is used for indirect etching to form a continuous arc-shaped thinning surface in the bending area. Chemical enhancement: using Na + K + The process involves a two-stage strengthening stepwise process: first, pre-strengthening is performed by holding the sodium salt system at 350℃~400℃ for 3min~6min, and then main strengthening is performed by holding the potassium salt system at 400℃~500℃ for 4min~8min. Polishing and cleaning: The strengthened glass is precision polished to a surface roughness of <0.01μm, and then cleaned and dried.
[0012] According to the technical solution provided in this application, the thickness distribution of the arc-shaped thinning structure and the size of the elongated through-holes in the metal support plate layer are determined according to the following collaborative design rules: Using the thickness of the ultrathin flexible glass layer as the independent variable and the width and length of the long through hole as the dependent variables, a thickness-hole size response surface model was established through DOE experiments to obtain the optimal parameter combination that minimizes the crease depth after 400,000 bends. When the thickness of the ultrathin flexible glass layer is 25μm, the width of the elongated through hole is 80μm and the length is 6mm; when the thickness of the ultrathin flexible glass layer is 30μm, the width of the elongated through hole is 100μm and the length is 8mm. For other thickness values of the ultrathin flexible glass layer, the corresponding optimal elongated through-hole size is determined by interpolation using the response surface model.
[0013] According to the technical solution provided in this application, the construction and updating of the response surface model includes the following steps: Initial modeling stage: The thickness of the ultrathin flexible glass layer, the width and length of the long through hole are used as input parameters, and the crease depth and light transmittance attenuation after 400,000 bends are used as output indicators. An initial response surface model is established based on the initial DOE experimental data. Process execution stage: Based on the optimal parameter combination output by the initial response surface model, namely the optimal matching value between the thickness of the ultrathin flexible glass layer and the width and length of the elongated through hole, the ultrathin flexible glass layer is prepared and the metal support plate layer is assembled. Feedback acquisition phase: Dynamic bending test is performed on the prepared support plate structure to collect the actual crease depth and light transmittance attenuation, and the deviation between them and the model prediction value is calculated; Model correction stage: The deviation and the corresponding process parameters are used as new sample points, and the response surface model is updated using the Bayesian regularization method to obtain the corrected model, so that the prediction accuracy of subsequent batches is gradually improved. Repeat the steps of the above process execution stage, feedback acquisition stage, and model correction stage to enable the response surface model to continuously evolve during continuous production until the deviation between the actual value and the predicted value converges to within the preset allowable range.
[0014] According to the technical solution provided in this application, the following steps are also included: Based on multiple bending test data of the best batch of support plate samples in history, a standard growth curve of crease depth with the number of bends was pre-calibrated. The curve shows that the crease grows rapidly in the early stage of bending and gradually slows down and stabilizes in the later stage of bending. The support plate samples for the current batch are prepared based on the optimal parameter combination output by the response surface model, and dynamic bending tests are performed on the samples for the current batch. The number of bends and the corresponding crease depth are monitored in real time, and the measured crease growth curve for the current batch is generated. The measured crease growth curve is compared with the standard growth curve, and the crease depth deviation between the two under the same number of bends is calculated. If the crease depth deviation exceeds a preset threshold, it is determined that the process parameter combination of the current batch deviates from the historical optimal level. The crease depth deviation and the corresponding process parameters are then used as new sample points to trigger the response surface model to be corrected again in order to recalculate the optimal parameter combination.
[0015] Compared with the prior art, the beneficial effects of this application are as follows: I. Significantly Improved Crease Performance: This application replaces the traditional PI layer with a chemically strengthened ultrathin flexible glass layer. Utilizing the inherent properties of UTG material's high elastic modulus and excellent dimensional stability, it can rapidly recover its elasticity after bending, minimizing irreversible plastic deformation. Simultaneously, the bending area of the UTG layer is designed with a continuous arc-shaped thinning structure, ensuring that the thickness at the center line of the bending area is less than the edge thickness. This avoids stress concentration caused by abrupt thickness changes and further disperses bending stress. The synergistic effect of these materials and structures significantly reduces the crease depth of the foldable screen after repeated bending, resulting in a significant improvement in the screen's visual flatness.
[0016] Second, enhanced bending reliability: The UTG layer undergoes chemical strengthening treatment, resulting in high surface hardness and bending fatigue strength; multiple elongated through-holes spaced along the bending direction are opened in the folding area of the metal support plate layer, effectively improving folding flexibility while ensuring support rigidity; the first and second foldable adhesive layers use acrylic flexible adhesives, exhibiting excellent adhesion compatibility with the UTG layer and metal support plate layer. This multi-layered structure collectively ensures the structural integrity and interlayer stability of the support plate during long-term high-frequency bending, avoiding failure issues such as interlayer delamination.
[0017] Third, the structure is simple and easy to industrialize. This application retains the existing support plate stacked structure, only replaces the PI layer with the UTG layer, and is equipped with easy-to-process structural features such as arc-shaped thinning and long through holes. It does not require major modification to the production line and has high industrialization feasibility and cost advantages. Attached Figure Description
[0018] Other features, objects, and advantages of this application will become more apparent from the following detailed description of non-limiting embodiments with reference to the accompanying drawings: Figure 1 A structural schematic diagram of the support plate structure provided in this application; The text labels in the image represent: 1. First foldable adhesive layer; 2. Ultra-thin flexible glass layer; 3. Second foldable adhesive layer; 4. Metal support plate layer; 5. Hole-masking tape layer. Detailed Implementation
[0019] The present application will now be described in further detail with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative of the invention and not intended to limit it. Furthermore, it should be noted that, for ease of description, only the parts relevant to the invention are shown in the accompanying drawings.
[0020] It should be noted that, unless otherwise specified, the embodiments and features described in this application can be combined with each other. This application will now be described in detail with reference to the accompanying drawings and embodiments.
[0021] Example 1 As mentioned in the background section, this application proposes a support plate structure, such as... Figure 1 As shown, it includes: A multi-layer composite support plate is disposed on the back side of the OLED screen of the foldable screen; it includes, in sequence from the side closest to the OLED screen to the side furthest from the OLED screen: A first foldable adhesive layer 1 is bonded to the OLED screen body on one side. An ultra-thin flexible glass layer 2 is provided, one side of which is bonded to the other side of the first foldable adhesive layer 1. This ultra-thin flexible glass layer 2 is also known as a UTG layer (abbreviated as UTG, full name: Ultra-Thin Glass). The bending area of the UTG layer employs an arc-shaped thinning structure, with the thickness change of the thinning surface being a continuous arc rather than an abrupt change, to reduce stress concentration during bending. The UTG layer replaces the PI layer in traditional laminated structures.
[0022] The second foldable adhesive layer 3 is bonded to the other side of the ultrathin flexible glass layer 2 on one side. Metal support plate layer 4, one side of which is bonded to the other side of the second foldable adhesive layer 3; Hole-masking tape layer 5, one side of which is bonded to the other side of the metal support plate layer 4; The masking tape layer 5 uses a polyester film substrate with a thickness of 10-20μm. Its surface has a light-shielding coating with a light-shielding rate of ≥98%. It is used to shield the perforated structure of the metal support plate layer 4, preventing light leakage from affecting the display effect. The polyester film can be biaxially oriented polyethylene terephthalate film, such as Mylar.
[0023] The ultra-thin flexible glass layer 2 is chemically strengthened, and the bending area of the ultra-thin flexible glass layer 2 is set as a continuous arc-shaped thinning structure extending along the bending direction. The thickness of the arc-shaped thinning structure at the center line of the bending area is less than its thickness at the edge. The folded area of the metal support plate layer 4 is provided with a plurality of elongated through holes arranged at intervals along the bending direction. Both the first foldable adhesive layer 1 and the second foldable adhesive layer 3 are acrylic flexible adhesives.
[0024] In a preferred embodiment, the thickness of the ultrathin flexible glass layer 2 is 20μm to 40μm, and the surface compressive stress of the ultrathin flexible glass layer 2 after chemical strengthening treatment is ≥600MPa and the Vickers hardness is ≥500HV.
[0025] In a preferred embodiment, the width of the bending area of the arc-shaped thinning structure is 5mm to 40mm, the minimum thickness of the arc-shaped thinning structure at the center line of the bending area is 20μm to 30μm, and the edge thickness of the arc-shaped thinning structure is 40μm.
[0026] In a preferred embodiment, the metal support plate layer 4 is made of foldable SUS 316L stainless steel or TA4 titanium alloy. SUS 316L stainless steel contains 2%–3% molybdenum and possesses excellent corrosion resistance and bending fatigue strength. TA4 titanium alloy is lightweight and high-strength, with a density ≤4.5 g / cm³. 3 Furthermore, the tensile strength is ≥860MPa; the width of the elongated through-hole is 50μm~150μm, and the length is 4mm~12mm. The folding area of the metal support plate layer 4 is designed with an elongated hole structure, with a hole width of 50-150μm and a hole length of 4-12mm, to improve folding flexibility and ensure support strength.
[0027] In a preferred embodiment, the thickness of both the first foldable adhesive layer 1 and the second foldable adhesive layer 3 is 5μm to 15μm, and their glass transition temperature is ≤-20℃ and their elongation at break is ≥300%. This ensures that they maintain good flexibility and adhesive stability in low-temperature to room-temperature environments, avoiding interlayer delamination.
[0028] Example 2 This embodiment proposes a foldable screen, including an OLED screen body and a support plate structure as described in Embodiment 1 disposed on the back side of the OLED screen body.
[0029] The total thickness of the support plate structure is controlled between 220-320μm to ensure it meets the thinness and lightness requirements of foldable screens while also satisfying the rigidity requirements. This application also protects the application of the aforementioned support plate structure in flexible OLED foldable screens. Through the high elastic modulus and dimensional stability of the UTG layer, the support plate structure uniformly disperses stress during bending, allowing the foldable screen to maintain a crease depth ≤5μm and transmittance attenuation ≤3% after 400,000 180° bending cycles at a bending radius of 1.5mm, far exceeding the performance of traditional PI layer structures. The beneficial effects of this application are: Significantly improved crease performance: UTG material has excellent elastic recovery performance and dimensional stability. Compared with PI layer, it is less likely to produce irreversible wrinkles and plastic deformation after high-frequency bending. Combined with the arc-shaped thinning design of the bending area, stress concentration is further dispersed, which greatly reduces the crease depth and improves the visual flatness of the screen.
[0030] Enhanced bending reliability: The chemically reinforced UTG layer has high surface hardness and bending fatigue strength. Within the thickness range of 20-40μm, it can achieve more than 400,000 bending cycles without cracking, and its service life is increased by more than 50% compared with traditional structures. At the same time, the UTG layer and the flexible adhesive layer have good compatibility, avoiding the problem of interlayer delamination caused by long-term bending.
[0031] Optical performance optimization: The UTG layer has a light transmittance of ≥92% and a haze of ≤1.5%, which significantly improves the display clarity and color reproduction of the screen compared to the plastic texture of the PI layer; combined with the high light-blocking rate of the hole-masking tape layer 5, the display effect is further optimized.
[0032] High feasibility for industrialization: The preparation process of the UTG layer has achieved a breakthrough in domestic production, and it can be mass-produced through existing mature processes such as chemical strengthening and selective thinning, with a yield of ≥85%; at the same time, the solution to replace the PI layer does not require major modifications to the existing support plate production line, but only requires adjustment of the adhesive layer adaptation parameters, which reduces the cost of industrialization.
[0033] Example 3 This application proposes a method for preparing an ultrathin flexible glass layer 2 in the support plate structure as described above, comprising the following steps: Substrate pretreatment: Select raw glass substrates with a thickness of 50μm to 160μm and perform ultrasonic cleaning; Selective thinning: A mask is attached to the surface of the substrate, and fluoride coatings of different thicknesses are formed in the bending area through laser drilling and coating treatment. Then, hydrochloric acid mist is used for indirect etching to form a continuous arc-shaped thinning surface in the bending area. Chemical enhancement: using Na + K +The process involves a two-stage strengthening stepwise process: first, pre-strengthening is performed by holding the sodium salt system at 350℃~400℃ for 3min~6min, and then main strengthening is performed by holding the potassium salt system at 400℃~500℃ for 4min~8min. Polishing and cleaning: The strengthened glass is precision polished to a surface roughness of <0.01μm, and then cleaned and dried.
[0034] In a preferred embodiment, the thickness distribution of the arc-shaped thinning structure and the size of the elongated through-holes in the metal support plate layer 4 are determined according to the following collaborative design rules: Using the thickness of the ultrathin flexible glass layer 2 as the independent variable and the width and length of the elongated through hole as the dependent variables, a thickness-hole size response surface model was established through DOE experiments to obtain the optimal parameter combination that minimizes the crease depth after 400,000 bends. When the thickness of the ultrathin flexible glass layer 2 is 25μm, the width of the elongated through hole is 80μm and the length is 6mm; when the thickness of the ultrathin flexible glass layer 2 is 30μm, the width of the elongated through hole is 100μm and the length is 8mm. For other thickness values of the ultrathin flexible glass layer 2, the corresponding optimal elongated through-hole size is determined by interpolation using the response surface model.
[0035] Specifically, in the selective thinning step, a continuous arc-shaped thinning surface is formed in the bending area of the ultrathin flexible glass layer 2 through masking, laser drilling, coating, and hydrochloric acid etching. The thickness distribution of this arc-shaped thinning surface is not uniform, but gradually decreases from the edge to the center line, with the thickness being the smallest at the center line. At the same time, the metal support plate layer 4 has multiple elongated through holes spaced apart along the bending direction in its folded area. The function of these through holes is to reduce the bending stiffness of the folded area and improve the folding flexibility. However, simply thinning the ultrathin flexible glass layer 2 or simply creating elongated through holes cannot guarantee the minimization of the crease depth after bending. Through a large number of experiments, it was found that there is a significant synergistic effect between the thickness of the ultrathin flexible glass layer 2 and the width and length of the elongated through holes: when the two dimensions are properly matched, the bending stress can be more evenly distributed between the ultrathin flexible glass layer 2 and the metal support plate layer 4, thereby significantly reducing the crease depth after 400,000 bends.
[0036] Based on the above findings, this embodiment proposes a collaborative design rule. First, the thickness of the ultra-thin flexible glass layer 2 is used as the independent variable, and the width and length of the elongated through-hole are used as the dependent variables. The independent variable refers to the independently changing parameters; here, the thickness of the ultra-thin flexible glass layer 2 can be selected within the range of 20 to 40 micrometers according to the requirements of different foldable screen products. The dependent variable is the target parameter that needs to be determined based on the independent variable. To establish a quantitative relationship between thickness and hole size, a Design of Experiments (DOE) experiment is used. DOE experiments, by systematically changing the levels of multiple factors and analyzing the results using statistical methods, can efficiently find the optimal parameter combination.
[0037] In practice, at least three different thicknesses of the ultrathin flexible glass layer 2 are selected, such as 25 μm, 30 μm, and 35 μm. For each thickness value, multiple sets of support plate samples with different through-hole widths (e.g., 50 μm, 80 μm, 100 μm, 120 μm, 150 μm) and through-hole lengths (e.g., 4 mm, 6 mm, 8 mm, 10 mm, 12 mm) are prepared. These samples are then subjected to 400,000 180-degree bend tests at a bending radius of 1.5 mm, and the crease depth after each bend is measured. Based on the test results, a response surface model can be established. A response surface model is a mathematical statistical model that describes the approximate functional relationship between input variables (thickness, hole width, hole length) and output response (crease depth). Using this model, the optimal hole width and hole length that minimize the crease depth can be calculated.
[0038] This embodiment presents two specific optimization results: when the thickness of the ultrathin flexible glass layer 2 is 25 micrometers, the optimal width of the elongated through-hole is 80 micrometers and the length is 6 millimeters; when the thickness of the ultrathin flexible glass layer 2 is 30 micrometers, the optimal width of the elongated through-hole is 100 micrometers and the length is 8 millimeters. For other thickness values, such as 22 micrometers, 28 micrometers, and 35 micrometers, interpolation calculations can be performed using a response surface model. Interpolation refers to the method of estimating the optimal value for an unknown thickness using known discrete data points (the optimal values corresponding to 25 micrometers and 30 micrometers). For example, for a thickness of 28 micrometers, the corresponding hole width and length can be obtained by linear interpolation or quadratic interpolation based on the response surface curves of 25 micrometers and 30 micrometers. In this way, it is not necessary to re-perform a complete DOE experiment for each thickness value, and the co-optimal parameters can be obtained quickly, greatly improving the efficiency of process development.
[0039] In a preferred embodiment, the construction and updating of the response surface model includes the following steps: Initial modeling stage: The thickness of the ultrathin flexible glass layer 2, the width and length of the elongated through hole are used as input parameters, and the crease depth and light transmittance attenuation after 400,000 bends are used as output indicators. An initial response surface model is established based on the initial DOE experimental data. Process execution stage: Based on the optimal parameter combination output by the initial response surface model, namely the optimal matching value between the thickness of the ultrathin flexible glass layer 2 and the width and length of the elongated through hole, the ultrathin flexible glass layer 2 is prepared and the metal support plate layer 4 is assembled. Feedback acquisition phase: Dynamic bending test is performed on the prepared support plate structure to collect the actual crease depth and light transmittance attenuation, and the deviation between them and the model prediction value is calculated; Model correction stage: The deviation and the corresponding process parameters are used as new sample points, and the response surface model is updated using the Bayesian regularization method to obtain the corrected model, so that the prediction accuracy of subsequent batches is gradually improved. Repeat the steps of the above process execution stage, feedback acquisition stage, and model correction stage to enable the response surface model to continuously evolve during continuous production until the deviation between the actual value and the predicted value converges to within the preset allowable range.
[0040] Specifically, the response surface model is a one-time model built based on initial DOE experimental data. However, in actual production, due to factors such as raw material batch fluctuations, process parameter drift, and environmental changes, the bending performance of products produced according to the initial model may not consistently meet expectations. Therefore, this embodiment proposes a closed-loop feedback optimization method, enabling the response surface model to continuously self-correct and evolve during continuous production.
[0041] Specifically, the process includes the following stages. The first stage is the initial modeling stage. In this stage, the input parameters and output indicators are first determined. The input parameters include the thickness of the ultrathin flexible glass layer 2, and the width and length of the elongated through-hole. The thickness is generally selected from a target value between 20 micrometers and 40 micrometers, the hole width is selected from 50 micrometers to 150 micrometers, and the hole length is selected from 4 millimeters to 12 millimeters. The output indicators are the crease depth and transmittance attenuation after 400,000 bends. Transmittance attenuation refers to the percentage decrease in transmittance of the ultrathin flexible glass layer 2 before and after bending, which reflects the degree of microcrack formation inside the glass. Based on the initial DOE experimental data, such as multiple sets of (thickness, hole width, hole length) and corresponding (crease depth, transmittance attenuation) data points obtained according to the orthogonal experimental scheme described earlier, an initial response surface model is established using regression analysis. The second stage is the process execution stage. According to the initial response surface model, the desired thickness of the ultrathin flexible glass layer 2 (e.g., 28 micrometers) is input, and the model will output the optimal hole width and hole length that minimize the crease depth. Then, the ultrathin flexible glass layer 2 is prepared according to this set of optimal parameters (including substrate pretreatment, selective thinning, chemical strengthening, polishing and cleaning, etc.) and the metal support plate layer 4 is assembled (including long through-hole processing, bonding, etc.). The third stage is the feedback acquisition stage. Dynamic bending tests are performed on the prepared support plate structure. Dynamic bending test refers to fixing the support plate on a dedicated bending test machine and repeatedly bending it at a set bending radius (e.g., 1.5 mm), bending angle (180 degrees) and frequency (e.g., once per second), and measuring the crease depth and transmittance attenuation in real time or periodically. After the test, the actual measured crease depth and transmittance attenuation values are obtained. These two actual values are compared with the crease depth and transmittance attenuation values predicted by the initial response surface model, and the deviation is calculated. The deviation can be an absolute difference or a relative percentage. The fourth stage is the model correction stage. The calculated deviation and the corresponding process parameters (i.e., the actual thickness, hole width, and hole length used in this batch) are added as a new sample point to the original DOE experimental dataset. Then, the response surface model is updated using Bayesian regularization. Bayesian regularization is a regression technique that prevents overfitting. It limits excessive fluctuations in model coefficients by adding a penalty term to the loss function, thus maintaining the model's stability and generalization ability while fitting new data. Compared to ordinary least squares regression, Bayesian regularization can more effectively handle small sample data and noisy data, making it particularly suitable for scenarios where data is gradually accumulated during production. After updating with Bayesian regularization, the corrected response surface model is obtained, denoted as the corrected model. The corrected model will improve the prediction accuracy for subsequent batches. Finally, the three stages of process execution, feedback collection, and model correction are repeated to form an iterative loop. Each loop adds a new real production data point to the dataset, thus updating the response surface model.As production batches increase, the model contains more and more information, and the deviation between its predictions and actual results gradually decreases. When the deviation converges to within a preset allowable range, such as a crease depth deviation of less than 0.5 micrometers and a transmittance attenuation deviation of less than 0.5%, the model can be considered sufficiently accurate, and iteration can be stopped or the update frequency reduced.
[0042] In a preferred embodiment, the following steps are also included: Based on multiple bending test data of the best batch of support plate samples in history, a standard growth curve of crease depth with the number of bends was pre-calibrated. The curve shows that the crease grows rapidly in the early stage of bending and gradually slows down and stabilizes in the later stage of bending. The support plate samples for the current batch are prepared based on the optimal parameter combination output by the response surface model, and dynamic bending tests are performed on the samples for the current batch. The number of bends and the corresponding crease depth are monitored in real time, and the measured crease growth curve for the current batch is generated. The measured crease growth curve is compared with the standard growth curve, and the crease depth deviation between the two under the same number of bends is calculated. If the crease depth deviation exceeds a preset threshold, it is determined that the process parameter combination of the current batch deviates from the historical optimal level. The crease depth deviation and the corresponding process parameters are then used as new sample points to trigger the response surface model to be corrected again in order to recalculate the optimal parameter combination.
[0043] Specifically, extensive experiments revealed that the crease depth of the support plate structure prepared using the optimal parameter combination does not increase linearly with the number of bends. Instead, it exhibits a saturation characteristic of rapid initial growth followed by a gradual slowdown and eventual stabilization. For example, in Example 5, the crease depth was 2.3 micrometers after 200,000 bends and 4.1 micrometers after 500,000 bends. The increase in the last 300,000 bends was only 1.8 micrometers, far less than the 2.3 micrometer increase in the first 200,000 bends. This pattern indicates that there is a limit to the crease depth, and the bending life mainly depends on the damage accumulation in the initial stage. Utilizing this pattern, process anomalies can be detected earlier, avoiding problems only being discovered after 400,000 bends have been completed.
[0044] The specific steps of this embodiment are as follows. First, based on multiple bending test data of the historically optimal batch of support plate samples, a standard growth curve of crease depth with the number of bends is pre-calibrated. The historically optimal batch refers to the batch prepared according to the co-design rules and whose performance has been fully verified (such as the optimal parameter combination in Example 4 or Example 5). Dynamic bending tests are performed on this batch of samples. During the bending process, the crease depth is measured every certain number of bends (e.g., every 10,000 or 20,000 bends), and the data points of the number of bends and the corresponding crease depth are recorded. These data points are plotted on a coordinate system and plotted using a suitable function (e.g., an exponential function δ = δ_max × (1 - e^(-δ_max))). {-αN} A smooth standard growth curve is obtained by fitting a curve (where δ is the crease depth, N is the number of bends, δ_max is the maximum crease depth, and α is the attenuation coefficient). This curve intuitively reflects the evolution of crease depth under ideal process conditions: in the early stage of bending (the first 100,000 bends), the curve slope is large, and the crease depth increases rapidly; in the middle stage of bending (100,000 to 300,000 bends), the slope gradually decreases; in the later stage of bending (after 300,000 bends), the curve tends to be horizontal, and the crease depth approaches the maximum value.
[0045] The second step involves preparing support plate samples for the current batch based on the optimal parameter combination output by the current response surface model. It's important to note that while the parameter combination for the current batch may be identical to the historical best combination, random fluctuations during production may cause the actual product's bending performance to deviate from the historical best. Dynamic bending tests are then conducted on the samples for the current batch, using the same test conditions (bending radius, angle, frequency) as the calibration standard curve, and the number of bends and the corresponding crease depth are monitored in real time. Monitoring can be performed using an online optical measurement device, automatically capturing images of the screen surface in the unfolded state during each bending cycle, and calculating the crease depth using image processing algorithms. Connecting the monitored data points generates the measured crease growth curve for the current batch.
[0046] The third step is to compare the measured crease growth curve with the standard growth curve. The specific method is as follows: under the same number of bends (e.g., 50,000, 100,000, 150,000, 200,000, etc.), read the crease depth values on the standard curve and the measured curve, and calculate the difference between the two, i.e., the crease depth deviation. Since the standard curve is a continuous function, while the measured curve consists of discrete points, interpolation can be performed on these discrete points before comparison. The deviation can be an absolute value or a relative deviation obtained by dividing by the standard value.
[0047] The fourth step involves setting a preset threshold, such as an absolute value of 0.5 micrometers for the crease depth deviation or a relative deviation of 15%. When the crease depth deviation exceeds this preset threshold after a certain number of bends, it is determined that the process parameter combination for the current batch has deviated from the historical optimal level. At this point, the crease depth deviation and the corresponding process parameters (i.e., the thickness, hole width, and hole length used in the current batch) are used as new sample points to trigger the response surface model to be corrected again. Specifically, this new sample point is added to the response surface model's dataset, Bayesian regularized regression is performed again to obtain an updated model, and the optimal parameter combination is recalculated using this model. Then, the process parameters for subsequent batches can be adjusted based on the recalculated parameter combination, or process corrections can be performed on the remaining samples in the current batch that have not yet undergone bending tests.
[0048] Example 4 Structural and performance verification based on SUS 316L stainless steel support plate: This embodiment is designed to meet the requirements of mid-to-high-end foldable screens for bending reliability and support strength. The basic structure from the inside out consists of: a first foldable adhesive layer 1, a UTG layer, a second foldable adhesive layer 3, a SUS 316L support plate layer (SUS316L stainless steel is selected as the metal support plate layer 4), and a hole-masking tape layer 5.
[0049] UTG thickness and bending hole morphology matching optimization: To achieve optimal adaptation between UTG thickness and the bending hole area of the SUS 316L support plate, and to improve overall bending flexibility and support stability, a horizontal orthogonal DOE experiment was conducted. The influencing factors were UTG thickness (factor A), width of the elongated hole in the support plate (factor B), and length of the elongated hole in the support plate (factor C). The response indicators were the crease depth, light transmittance attenuation, and bending life after 400,000 bends at a bending radius of 1.5 mm. The experimental parameters and optimal adaptation parameters are shown in the table below. Table 1
[0050] Through experimental optimization, the optimal matching parameter combination was determined to be: UTG thickness 30μm, hole width 100μm, and hole length 8mm. The matching logic for this combination is as follows: the 30μm UTG layer balances flexibility and rigidity, forming a reasonable stiffness gradient with the 0.12mm thickness of the SUS 316L support layer; the 100μm×8mm elongated hole structure can precisely distribute bending stress, avoiding folding jamming caused by excessively small hole width, and preventing insufficient support due to excessively large or long hole widths. The UTG layer fabrication process is simultaneously adapted to these parameters: a 100μm original glass substrate is selected, and after ultrasonic cleaning, masking, laser drilling (pulse energy 40μJ, pulse width 20ns, repetition frequency 30kHz, hole diameter 250μm, hole spacing 300μm), calcium fluoride coating, hydrochloric acid mist arc-shaped thinning etching, and polishing to a surface roughness of 0.008μm, a 30μm thick adaptive UTG layer is finally obtained.
[0051] Optimized compatibility between flexible adhesive and UTG bonding: To ensure the bonding stability between the flexible adhesive and the UTG layer and to prevent delamination during bending, a two-factor, three-level DOE experiment was conducted using plasma surface treatment. Plasma treatment power (factor D) and treatment time (factor E) were used as influencing factors, and an argon + oxygen mixed gas mixture (volume ratio 3:1) was employed. The response indices were delamination force and bending durability under different environments. The experimental parameter levels and optimal bonding parameters are shown in the table below. Table 2
[0052] After experimental optimization, the optimal bonding parameters were determined to be: 100W processing power and 60s processing time. The logic behind this parameter adaptation is that a 100W / 60s plasma treatment can form a uniform active layer on the UTG surface, ensuring molecular-level adhesion to acrylic adhesives without damaging the UTG surface structure due to over-treatment. Compared to other parameter combinations (such as 80W / 30s, peel force 1.2N / 25mm; 120W / 90s, peel force 1.6N / 25mm), the optimal parameters exhibit superior bonding stability.
[0053] Optimized compatibility between flexible adhesive and SUS 316L: To address the surface characteristics of SUS 316L metal, a multi-factor orthogonal DOE experiment was conducted involving "plasma treatment + bonding process" to ensure the reliability of adhesion with flexible adhesive. The experimental factors, levels, and optimal bonding parameters are shown in the table below. The response indicators are consistent with the UTG-adhesive bonding characterization (interlayer peel force and finished product bending durability under four environmental conditions). Table 3
[0054] Through experimental optimization, the optimal bonding parameter adaptation logic is as follows: an argon-oxygen ratio of 3:1 can accurately enhance the surface activity of SUS 316L, a bonding pressure of 0.3MPa and a speed of 10mm / s can ensure uniform spread of the adhesive layer, and a gap of 10μm can expel air bubbles. The three factors work together to ensure bonding stability.
[0055] Comprehensive performance verification: Performance tests were conducted on the optimized structure from the three angles mentioned above: At a bending radius of 1.5mm, after 400,000 180° bends at room temperature, the crease depth was 3.2μm, the light transmittance decreased by 2.1%, and there was no delamination between the flexible adhesive and the UTG and SUS 316L layers; After 400,000 bends under high temperature (85℃), high temperature and high humidity (85℃ / 85%RH), low temperature (-40℃), and thermal shock (-40℃-85℃, 100 cycles), the adhesion peel force of the two layers decreased by ≤15%, the crease depth was ≤3.5μm, and the light transmittance decreased by ≤2.5%. Compared to unoptimized structures (such as UTG 25μm + pore width 80μm + pore length 6mm, crease depth 4.5μm; without SUS plasma treatment, interlayer delamination occurs under high temperature and high humidity), the optimal fit combination significantly improves bending performance and bonding stability, and is superior to traditional PI layer structures (crease depth 8.5μm, light transmittance attenuation 5.3%, delamination after 300,000 bends).
[0056] Example 5: Structural and performance verification based on TA4 titanium alloy support plate: This embodiment is designed to meet the requirements of mid-to-high-end foldable screens for bending reliability and support strength. The basic structure from the inside out consists of: a first foldable adhesive layer 1, a UTG layer, a second foldable adhesive layer 3, a TA4 support plate layer (TA4 titanium alloy is selected as the metal support plate layer 4), and a hole-masking tape layer 5.
[0057] This embodiment is designed to meet the requirements of lightweight foldable screens. The basic structure, from the inside out, consists of: a first foldable adhesive layer 1 (acrylate adhesive, 8μm thick, T=-25℃, elongation at break 320%), a UTG layer (25μm thick, chemically strengthened, surface compressive stress 620MPa, bending zone width 15mm, centerline thickness 20μm, curved thinning transition), a second foldable adhesive layer 3 (same as the first foldable adhesive layer 1, 8μm thick), a TA4 titanium alloy support plate layer (0.1mm thick, density 4.4g / cm³, tensile strength 880MPa), and a hole-masking tape layer 5 (polyester substrate, 12μm thick, light-blocking rate 98.5%). Combining the lightweight and surface-active properties of TA4, a detailed explanation is provided from three core adaptation perspectives: UTG thickness and bending hole morphology matching optimization: To achieve bending adaptation between UTG and TA4 support plates while maintaining lightweight construction, a three-factor, three-level orthogonal DOE experiment was conducted. The influencing factors were UTG thickness (factor A), support plate hole width (factor B), and support plate hole length (factor C). The response indices were bending life, crease depth, and structural weight. The experimental parameter levels and optimal adaptation parameters are shown in the table below. Table 4
[0058] After experimental optimization, the optimal matching parameter combination is: UTG thickness 25μm, hole width 80μm, and hole length 6mm. The adaptation logic is as follows: the 25μm UTG layer further reduces weight compared to Example 1, matching the lightweight characteristics of 0.1mm TA4; the 80μm×6mm elongated hole structure ensures folding flexibility while avoiding a decrease in support force due to excessively large hole structure, ultimately achieving a 12% reduction in structural weight compared to Example 1, without compromising bending reliability.
[0059] Optimized compatibility between flexible adhesive and UTG bonding: Taking into account the characteristics of the 8μm thin adhesive layer, an optimization experiment was conducted on the adhesion between UTG and flexible adhesive. Plasma treatment was performed using an argon + oxygen mixed gas (volume ratio 2:1). A Design of Effect (DOE) experiment was conducted with treatment power (factor M) and treatment time (factor N) as two factors and three levels. The experimental parameter levels and optimal adhesion parameters are shown in the table below. Table 5
[0060] After optimization, the optimal parameter adaptation logic is: 2:1 argon-oxygen ratio and 100W / 60s processing parameters, which can form an active layer on the UTG surface that is compatible with the thin adhesive layer, ensuring the bonding strength of the thin adhesive layer, while avoiding over-processing that would cause UTG to become brittle, thus adapting to the bonding requirements of thinner and lighter structures.
[0061] Optimized compatibility between flexible adhesive and TA4: To address the high surface activity of TA4 titanium alloy, a DOE optimization experiment was conducted on the "plasma treatment + bonding process". The experimental factors, levels, and optimal bonding parameters are shown in the table below, and the response indicators are the same as before: Table 6
[0062] After optimization, the optimal bonding parameters are as follows: a 2:1 argon-oxygen ratio can moderately improve the surface activity of TA4; a low bonding pressure of 0.25MPa is suitable for the lightweight properties of TA4; and a speed of 12mm / s and a gap of 12μm ensure uniform spreading of the thin adhesive layer.
[0063] Comprehensive performance verification: Test results for the optimized structure at three angles: At a bending radius of 1.5mm, after 200,000 bends at room temperature, the crease depth is 2.3μm and the light transmittance decreases by 1.2%; after 500,000 bends, the crease depth is 4.1μm and the light transmittance decreases by 2.5%; after 500,000 bends under four durability conditions, there is no peeling between the two layers, the peel force decreases by ≤12%, and the crease depth is ≤4.3μm. This structure achieves both lightweight design and ensures bending reliability, which is superior to other parameter combinations in the same experiment (such as UTG 20μm + pore width 60μm + pore length 5mm, bending life is only 420,000 cycles; without TA4 plasma treatment, the peel force decreases by 35% under high temperature and high humidity).
[0064] Comparative experiment: Two traditional structures were selected as control groups: 1) "foldable adhesive / PI / foldable adhesive / SUS 316L / mylar hole-masking tape" structure; 2) "foldable adhesive / PI / foldable adhesive / TA4 / mylar hole-masking tape" structure; The structures of Example 4 (SUS316L+UTG) and Example 5 (TA4+UTG) of this application were used as experimental groups. Performance was compared under the same test conditions (1.5mm bending radius, 180° bending, frequency 1 time / second), and the results are shown in the table below: Table 7
[0065] The comparison results show that, regardless of whether SUS 316L or TA4 titanium alloy is used as the substrate of the support plate, the use of UTG layer to replace PI layer in this application significantly improves the crease performance, bending life, optical performance and surface hardness of the foldable screen; the TA4+UTG combination also takes into account the advantage of lightweighting. Both combinations have obvious technical advantages and can be adapted to foldable screen products with different needs.
[0066] The complete steps and procedures will be described in detail below: Step 1: Mask attachment and laser selective drilling (to achieve spatial distribution control of coating thickness) Substrate preparation: Select a raw glass substrate with a thickness of 100μm, clean it ultrasonically and dry it. Apply a 25μm thick acid-resistant PET mask to the surface of the substrate in the predetermined bending area (15mm wide).
[0067] Laser gradient patterning: A picosecond ultraviolet laser (wavelength 355nm, pulse energy 40μJ, pulse width 15ps) is used to fabricate an array pattern with continuously varying pore density and diameter on a mask. The specific design logic is as follows: during coating, the fluoride precursor can only be deposited on the glass surface through the mask openings; therefore, the local coating thickness can be precisely controlled by controlling the aperture ratio. The aperture ratio is highest at the center line of the bending area, gradually decreasing to zero towards the edges.
[0068] Table 8 Correspondence between Mask Laser Drilling Pattern and Coating Thickness
[0069] Note: The aperture ratio is the area ratio calculated based on the laser aperture and the center distance of the holes, and it is linearly proportional to the final coating thickness.
[0070] Gradient fluoride coating preparation: A substrate with a patterned mask was fed into a magnetron sputtering coating machine. Magnesium fluoride (MgF2) target with a purity of 99.99% was used for deposition under an argon atmosphere. The sputtering power was 300 W, and the deposition time was 15 minutes. After sputtering, the mask was removed. Step measurements confirmed the acquisition of a graded MgF2 coating with a thickness smoothly decreasing from 7.0 μm at the center to 0 μm at the edge, as shown in Table 8.
[0071] Step 2: Indirect etching with hydrochloric acid mist (to achieve a continuous arc-shaped profile) Etching Parameters and Control: The chemical principles and key process parameters for this step have been fully disclosed. The glass substrate with the gradient MgF2 coating is horizontally suspended above a temperature-controlled, sealed reaction chamber. The reservoir at the bottom of the chamber contains 37.5% (analytical grade) hydrochloric acid. The hydrochloric acid is heated and maintained at 30°C to generate saturated hydrochloric acid mist. The ambient temperature of the chamber is controlled at 35±1°C via an external jacket.
[0072] The etching process follows a two-step quantitative reaction mechanism: Acid-producing reaction: MgF2 coating + 2HCl(g) → MgCl2 + 2HF(g) Etching reaction: SiO2 (glass) + 4HF (g) → SiF4↑ + 2H2O (g) Quantitative relationship between etching rate and coating thickness: The concentration of HF gas generated by the acid-producing reaction is directly positively correlated with the local thickness of the MgF2 coating. After preliminary process calibration, at 35°C, the glass etching rate for every 1 μm thick MgF2 coating is approximately 0.17 μm / min. Based on this quantitative relationship, this embodiment controls the total etching time to 20 minutes to obtain accurate thickness distribution.
[0073] Table 9 Correspondence between Etching Parameters and Expected Etching Amount
[0074] Hydrochloric acid concentration: 37.5%, hydrochloric acid temperature: 30℃, cavity ambient temperature: 35℃, etching time: 20 minutes.
[0075] Ensuring and smoothing the curved profile: As shown in Table 9, because the etching rate gradually changes throughout the bending area, the glass substrate is naturally etched into a continuous curved surface that is thin at the center (26 μm) and thick at the edges (50 μm), without any steps or abrupt changes. Immediately after etching, the glass is precision polished using cerium oxide polishing slurry at a pressure of 0.12 MPa, a polishing disc speed of 50 rpm, and a polishing time of 4 minutes. After polishing, the surface roughness Ra, measured by atomic force microscopy (AFM), decreased from 0.15 μm after etching to 0.008 μm, ensuring the smoothness of the curved profile.
[0076] Step 3: Field Verification of the UTG Bending Zone Arc-Shaped Thinning Structure This embodiment provides measured thickness distribution data of the UTG bending region: using a spectral ellipsometry, the thickness of the UTG sample prepared above is scanned in a step of 0.5 mm along a direction perpendicular to the bending center line.
[0077] Table 10 Measured Data on Thickness Distribution in the Bending Zone of UTG
[0078] As shown in Table 10, the thickness of the UTG layer increases continuously and smoothly from 26.2 μm at the center to 50 μm at the edge, which is in line with the design expectations and there are no abrupt changes in thickness.
[0079] Performance counter-evidence: The UTG layer with the measured arc-shaped profile described above was assembled into a complete support plate structure according to the stacking scheme of Example 4 (matching an optimal hole width of 100μm and a hole length of 8mm using a SUS 316L support plate). After 400,000 bending tests at a bending radius of 1.5mm, the final crease depth was only 3.5μm, far lower than the control group (10.2μm) without arc-shaped thinning. This superior bending performance is determined by the mechanism of the arc-shaped thinning structure effectively dispersing stress, thus providing strong indirect evidence from a performance perspective.
[0080] The above description is merely a preferred embodiment of this application and an explanation of the technical principles employed. Those skilled in the art should understand that the scope of the invention involved in this application is not limited to technical solutions formed by specific combinations of the above-described technical features, but should also cover other technical solutions formed by arbitrary combinations of the above-described technical features or their equivalents without departing from the inventive concept. For example, technical solutions formed by substituting the above features with (but not limited to) technical features with similar functions disclosed in this application.
Claims
1. A support plate structure, characterized in that, include: A multi-layer composite support plate is located on the back side of the OLED screen of the foldable screen; From the side closest to the OLED screen to the side furthest away from the OLED screen, the following are included sequentially: The first foldable adhesive layer (1) is bonded to the OLED screen body on one side. An ultra-thin flexible glass layer (2) is bonded to the other side of the first foldable adhesive layer (1); The second foldable adhesive layer (3) is bonded to the other side of the ultra-thin flexible glass layer (2) on one side. Metal support plate layer (4), one side of which is bonded to the other side of the second foldable adhesive layer (3); A hole-masking tape layer (5) is bonded to the other side of the metal support plate layer (4) on one side. The ultra-thin flexible glass layer (2) is chemically strengthened, and the bending area of the ultra-thin flexible glass layer (2) is set as a continuous arc-shaped thinning structure extending along the bending direction. The thickness of the arc-shaped thinning structure at the center line of the bending area is less than its thickness at the edge. The folded area of the metal support plate layer (4) is provided with a plurality of elongated through holes arranged at intervals along the bending direction; Both the first foldable adhesive layer (1) and the second foldable adhesive layer (3) are acrylic flexible adhesives.
2. The support plate structure according to claim 1, characterized in that, The thickness of the ultrathin flexible glass layer (2) is 20μm to 40μm, and the surface compressive stress of the ultrathin flexible glass layer (2) after chemical strengthening treatment is ≥600MPa and the Vickers hardness is ≥500HV.
3. The support plate structure according to claim 1, characterized in that, The bending area width of the arc-shaped thinning structure is 5mm to 40mm, the minimum thickness of the arc-shaped thinning structure at the center line of the bending area is 20μm to 30μm, and the edge thickness of the arc-shaped thinning structure is 40μm.
4. The support plate structure according to claim 1, characterized in that, The metal support plate layer (4) is a foldable SUS316L stainless steel or TA4 titanium alloy. The SUS316L stainless steel has a molybdenum content of 2% to 3%, and the TA4 titanium alloy has a density of ≤4.5g / cm³ and a tensile strength of ≥860MPa. The width of the elongated through hole is 50μm to 150μm and the length is 4mm to 12mm.
5. The support plate structure according to claim 1, characterized in that, The thickness of the first foldable adhesive layer (1) and the second foldable adhesive layer (3) are both 5μm to 15μm, and their glass transition temperature is ≤-20℃ and their elongation at break is ≥300%.
6. A foldable screen, characterized in that, It includes an OLED screen body and a support plate structure as described in any one of claims 1 to 5 disposed on the back side of the OLED screen body.
7. A method for preparing an ultrathin flexible glass layer (2) in a support plate structure as described in claim 1, characterized in that, Includes the following steps: Substrate pretreatment: Select raw glass substrates with a thickness of 50μm to 160μm and perform ultrasonic cleaning; Selective thinning: A mask is attached to the surface of the substrate, and fluoride coatings of different thicknesses are formed in the bending area through laser drilling and coating treatment. Then, hydrochloric acid mist is used for indirect etching to form a continuous arc-shaped thinning surface in the bending area. Chemical enhancement: using Na + K + The process involves a two-stage strengthening stepwise process: first, pre-strengthening is performed by holding the sodium salt system at 350℃~400℃ for 3min~6min, and then main strengthening is performed by holding the potassium salt system at 400℃~500℃ for 4min~8min. Polishing and cleaning: The strengthened glass is precision polished to a surface roughness of <0.01μm, and then cleaned and dried.
8. The preparation method according to claim 7, characterized in that, The thickness distribution of the arc-shaped thinning structure and the size of the elongated through holes in the metal support plate layer (4) are determined according to the following collaborative design rules: Using the thickness of the ultrathin flexible glass layer (2) as the independent variable and the width and length of the long through hole as the dependent variable, a thickness-hole size response surface model was established through DOE experiments to obtain the optimal parameter combination that minimizes the crease depth after 400,000 bends. When the thickness of the ultrathin flexible glass layer (2) is 25 μm, the width of the elongated through hole is 80 μm and the length is 6 mm; when the thickness of the ultrathin flexible glass layer (2) is 30 μm, the width of the elongated through hole is 100 μm and the length is 8 mm. For other thickness values of the ultrathin flexible glass layer (2), the corresponding optimal elongated through-hole size is determined by interpolation using the response surface model.
9. The preparation method according to claim 8, characterized in that, The construction and updating of the response surface model includes the following steps: Initial modeling stage: The thickness of the ultrathin flexible glass layer (2), the width and length of the long through hole are used as input parameters, and the crease depth and transmittance attenuation after 400,000 bends are used as output indicators. An initial response surface model is established based on the initial DOE experimental data. Process execution stage: Based on the optimal parameter combination output by the initial response surface model, namely the optimal matching value between the thickness of the ultrathin flexible glass layer (2) and the width and length of the elongated through hole, the ultrathin flexible glass layer (2) is prepared and the metal support plate layer (4) is assembled. Feedback acquisition phase: Dynamic bending test is performed on the prepared support plate structure to collect the actual crease depth and light transmittance attenuation, and the deviation between them and the model prediction value is calculated; Model correction stage: The deviation and the corresponding process parameters are used as new sample points, and the response surface model is updated using the Bayesian regularization method to obtain the corrected model, so that the prediction accuracy of subsequent batches is gradually improved. Repeat the steps of the above process execution stage, feedback acquisition stage, and model correction stage to enable the response surface model to continuously evolve during continuous production until the deviation between the actual value and the predicted value converges to within the preset allowable range.
10. The preparation method according to claim 9, characterized in that, It also includes the following steps: Based on multiple bending test data of the best batch of support plate samples in history, a standard growth curve of crease depth with the number of bends was pre-calibrated. The curve shows that the crease grows rapidly in the early stage of bending and gradually slows down and stabilizes in the later stage of bending. The support plate samples for the current batch are prepared based on the optimal parameter combination output by the response surface model, and dynamic bending tests are performed on the samples for the current batch. The number of bends and the corresponding crease depth are monitored in real time, and the measured crease growth curve for the current batch is generated. The measured crease growth curve is compared with the standard growth curve, and the crease depth deviation between the two under the same number of bends is calculated. If the crease depth deviation exceeds a preset threshold, it is determined that the process parameter combination of the current batch deviates from the historical optimal level. The crease depth deviation and the corresponding process parameters are then used as new sample points to trigger the response surface model to be corrected again in order to recalculate the optimal parameter combination.
Citation Information
Patent Citations
Display panel
CN114078388A
Folding screen and manufacturing process therefor, and foldable electronic device
WO2024152712A1